2015
DOI: 10.1111/1556-4029.12938
|View full text |Cite
|
Sign up to set email alerts
|

Postmortem Aortic Dissection: An Artifact of the Embalming Process

Abstract: Aortic dissection (AD) is a serious condition that affects 3/100,000 individuals a year. Recently, a case report was published describing an embalmed patient with an aortic dissection. The purpose of this study was to examine the frequency of AD among 80 embalmed cadavers and confirm the AD with histopathologic evaluation. In seven cases of grossly identified AD, six were determined to be due to the embalming procedure and only one case of true antemortem AD was confirmed. These results suggest that aortic mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…The aforementioned case study prompted Rae et al to perform a retrospective study on eighty embalmed bodies to determine the frequency of aortic dissection with subsequent histological confirmation [6]. Seven of the eighty bodies were found to have an aortic dissection, however, only one was found to be a true antemortem aortic dissection based on the presence of an intramural hematoma on gross examination and confirmed histologically.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The aforementioned case study prompted Rae et al to perform a retrospective study on eighty embalmed bodies to determine the frequency of aortic dissection with subsequent histological confirmation [6]. Seven of the eighty bodies were found to have an aortic dissection, however, only one was found to be a true antemortem aortic dissection based on the presence of an intramural hematoma on gross examination and confirmed histologically.…”
Section: Discussionmentioning
confidence: 99%
“…In five cases, the aortic dissection was located around the embalming cannula. Rae et al concluded that mechanical separation of the aortic wall occurred during the embalming process, however they could not clearly identify if this was a result of flow of the embalming solution, or embalming solution-induced hardening and subsequent splitting of the aortic wall [6].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, little information is available that describes the uniqueness of the embalmed cadaveric lung. It has been shown that the embalming process causes artifacts (Rae et al 2015) and it is possible that embalming affects the gross presentation of all of the cadaveric organs.…”
Section: Introductionmentioning
confidence: 99%